Field of bones - Jance, Judith A. (Jance, Judith A. Joanna Brady mysteries, 2018)
This time Sheriff Joanna Brady may expect to see her maternity leave through to completion, but the world has other plans when a serial homicide case surfaces in her beloved Cochise County. Rather than staying home with her newborn and losing herself in the cold cases to be found in her father's long unread diaries, Joanna instead finds herself overseeing a complex investigation involving multiple jurisdictions.